The relation between human Y chromosome microdeletions and sperm morphology - (:unkn) unknown (My University, 2002)
Objective: Recent investigations have supported the importance of Y chromosome microdeletions in male infertility. Besides different factors, sperm morphology is also a very important component of the clinical evaluation of male fertility potential. The aim of our study was to understand the relation between Y chromosome microdeletions and sperm morphology in different risk groups. Material and Methods: In this study, 34 infertile men were selected and examined in terms of sperm morphology and Y chromosome microdeletions. Semen analyses of the patients were performed by using Strict criteria and the samples were grouped according to the sperm abnormalities. Peripheral blood samples were examined for Y chromosome microdeletions by a multiplex polymerase chain reaction amplification of sequence-tagged sites (STS) of the Y chromosome. Results: The incidence of deletions in the group was 14.7% (5/34). The rates of Y chromosome microdeletion were 33.3% for megalohead, 33.3% for elongehead, 0% for roundhead, 100% for pinhead, 14.3% for severe teratozoospermia, 33.3% for severe neck abnormalities and 0% for tail-stump. Pregnancy could not be obtained from Y chromosome deleted cases. Conclusion: It seems that especially patients with sperm head and neck abnormality have increased microdeletion risk. It is suggested that a detailed sperm morphology examination and classification is needed to clarify the Y chromosome deletion-sperm morphology relation.
Keywords: Male infertility; Sperm morphology; Y chromosome microdeletions